2012
DOI: 10.1089/thy.2011.0173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iodine and Thyroid Cancer Risk in French Polynesia: A Case–Control Study

Abstract: French Polynesia is a mild iodine deficiency area in which a higher consumption of food from the sea and a higher dietary iodine intake are significantly associated with a decreased risk of thyroid cancer. The quantification of this reduction requires specific investigation of iodine intake in traditional Polynesian food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 24 publications
4
70
1
6
Order By: Relevance
“…Lastly, we estimated that traditional Polynesian dietary pattern was associated with a lower thyroid cancer incidence than western pattern (Clero et al, 2012a). French Polynesia is a mild iodine deficiency area in which a higher consumption of food from the sea and a higher dietary iodine intake are significantly associated with a decreased risk of thyroid cancer (Clero et al, 2012b). In this report we investigated the potential risk factors that have not been previously reported.…”
Section: Introductionmentioning
confidence: 93%
“…Lastly, we estimated that traditional Polynesian dietary pattern was associated with a lower thyroid cancer incidence than western pattern (Clero et al, 2012a). French Polynesia is a mild iodine deficiency area in which a higher consumption of food from the sea and a higher dietary iodine intake are significantly associated with a decreased risk of thyroid cancer (Clero et al, 2012b). In this report we investigated the potential risk factors that have not been previously reported.…”
Section: Introductionmentioning
confidence: 93%
“…The increasing trend of obesity might be another factor that accounts for some of the observed increasing incidence of thyroid cancer, although the degree of its contribution is unclear. Both deficiency and overconsumption of iodine have been suggested to be risk factors for thyroid cancer, although the results from epidemiologic studies have been inconsistent (28)(29)(30). Based on the data from the National Health and Nutrition Examination Survey (NHANES), urinary iodine measurements have shown that the general U.S. population is iodine sufficient, although urinary iodine levels decreased by more than 50% between 1971 and 1974 and 1988 and 1994, and have remained stable since 2000 (31,32).…”
Section: Thyroid Cancer Epidemic 477mentioning
confidence: 99%
“…Our objective was to examine the association between fingernail selenium concentrations and thyroid cancer in French Polynesia, a country highly exposed to selenium mainly through fish consumption and characterized by mild iodine deficiency (Clero et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other biomarker measures of selenium, such as blood or urine, nail concentrations represent longer-term exposure, typically the previous three to six months. This case-control study has already shown that a high number of pregnancies (Brindel et al, 2008), tallness and obesity (Brindel et al, 2009;Clero et al, 2010), familial history of thyroid cancer , low dietary intake of iodine (Clero et al, 2012), poor economic conditions , and nuclear radiation fallout , having a spring as the main source of drinking water (Xhaard et al, 2014) are thyroid cancer risk factors in French Polynesia.…”
Section: Introductionmentioning
confidence: 95%